Where ? When ? And how often ? What can we learn about daily urban mobilities from Twitter data and Google POIs in Bangkok (Thailand) and which perspectives for dengue studies ? - Alexandre Cebeillac; Eric Daudé; Thomas Huraux (Netcom)
Human mobilities in urban areas have an impact on the spread of infectious diseases, including those caused by mosquito-borne diseases like dengue and Zika virus. Therefore, finding appropriate data and methods to perform spatial analyses of mobilities is a critical issue. The emergence of substantial amount of geolocated data, which is easily available on the Internet, has a great potential in mobility researches, especially when paired with land use, following the activity-space concept. This paper, focused on the dengue endemic mega-city of Bangkok (Thailand), explores the potentialities of (A) using a land use classification from Google’s points of interest (POIs) to assess the likelihood of performing an activity from (B) a large dataset of individual geolocated tweets to characterize and quantify daily mobility. These emerging data sources allow the characterization of (C) the rhythms of daily mobility in Bangkok, from the perspective of (1) the macroscopic urban pulse and (2) the rhythms and aims for individual movement. The advantages and limitations of this kind of data will be finally discussed regarding dengue epidemics.